Seasonal assessment of pollution status, bioaccumulation and potential human health risk of heavy metals in Shrimps (Penaeus Monodon) and water from the Great Kwa River in Calabar, Nigeria. (African Journal of Biomedical Research, 2024)
The deterioration of water quality in rivers is caused by various factors, with heavy metals contamination being a significant contributor. Human activities are identified as the main cause of this contamination. This research evaluated the pollution levels, bioaccumulation, and potential health risks associated with heavy metals presence in Shrimps (Penaeus Monodon) and the water from Great Kwa River in Calabar, Nigeria. Shrimp and water samples were collected for both wet and dry season at four designated locations along the river. The physical characteristics of the water were assessed in-situ. The concentrations of heavy metals, namely lead, cadmium, chromium, cobalt, iron, and copper were determined through wet digestion and analyzed using an Atomic Absorption Spectrophotometer. To validate the method, standard reference materials (Lichens coded IAEA - 336) were utilized. The physical properties of water were found to be within the established standards. In the shrimp, the Fe and Pb were significantly higher (p < 0.05) during the wet season compared to the dry season. Similarly, the occurrence of Fe, Cr, and Pb in the water samples was significantly higher (p < 0.05) during the wet season compared to the dry season. The Estimated Daily Intake of all the assessed metals in both seasons were within the recommended upper tolerable limits for heavy metals in seafoods. The Target Hazard Quotients for metals under investigation were also within safe limits for both seasons. The Hazard Indices of these metals in both seasons were less than one (